Predicting rock strength anisotropy using a sensitivity-driven evolutionary polynomial regression - Stephane A. R. Cerrato; Guilherme J. C. Gomes; Ruan G. S. Gomes; Eurípedes A. Vargas; Pedro Cacciari (Bulletin of Engineering Geology and the Environment, 2026)
The strength of anisotropic rocks remarkably depends on the orientation of stresses with respect to existing directional features in rocks such as foliation, bedding planes, and cleavages. While rock strength anisotropy is crucial for engineering design, experimental tests to obtain peak strengths of samples with several degrees of anisotropy and confining stresses are time-consuming and costly. Reliable and high-fidelity models derived with soft computing techniques can be applied to estimate rock strength anisotropy. Using a data set containing samples from 15 transversely isotropic rocks, this work developed a sensitivity-driven evolutionary polynomial regression (EPR) model to predict transverse isotropic strength. The model computes the peak strength, $$\:{σ\:}_{1}$$ , as a function of confining stress, $$\:{σ\:}_{3}$$ , orientation angle, $$\:β\:$$ , degree of anisotropy, $$\:R$$ , and parameters of the Hoek-Brown strength criterion, $$\:{m}_{i}$$ and $$\:{σ\:}_{ci}$$ . The developed model showed parsimony (lower number of parameters and input variables), good predictive capability (accurately tracks observed peak strengths) and generalization ability (physical meaning). Sensitivity analysis revealed that the model can adequately simulate the U-shaped anisotropy curves and capture non-linear relationships between $$\:{σ\:}_{1}$$ and other inputs ( $$\:{σ\:}_{3}$$ , $$\:β\:$$ , $$\:{m}_{i}$$ and $$\:{σ\:}_{ci}$$ ), but it is less sensitive to $$\:R$$ . Moreover, our modeling approach benefits from Monte Carlo simulations to explore the uncertainty involved in the input–output relationships. Comparison of simulated peak strengths with results of recent models published in the literature further supported the ability of our optimal EPR model structure. The proposed model could be a useful approach for estimating the strength of transversely isotropic rocks.

Landscape analysis and Connectivity Index to assess debris flows susceptibility of recently deglaciated catchment (Presanella Group, Rhaetian Alps) - M.C. Salvatore; R. Cerrato; L. Alderighi; M. Della Seta; C. Baroni (CATENA, 2026)

Conference Report: Cerebellar Development and Disease at Single-Cell Resolution - Lena M. Kutscher; Davide Aprile; N. Sumru Bayin; Esther B. E. Becker; Valentina Cerrato; Giacomo Turrini; Marion Coolen; Vincent Cantagrel; Béatrice C. Durand; Myron K. Evans II; Parthiv Haldipur; Kathleen J. Millen; et al. (The Cerebellum, 2025)

Correction: Salinity tolerance of two critically endangered endemic species and its implications for distribution and conservation of model microinsular Mediterranean species - C. Cardona; I. Cortés-Fernández; M. D. Cerrato; L. Gil (Plant Ecology, 2025)

Salinity stress on three representative species from Mediterranean semifixed dunes: Assessment of salinity exposure and substrate conductivity data reveal variable response strategies and tolerance between species - M.D. Cerrato; P.M. Mir-Rosselló; I. Cortés-Fernández; A. Ribas-Serra; C. Cardona; A. Sureda; J. Flexas; L. Gil (Science of The Total Environment, 2024)

Response to Seawater Exposure During the Flowering Stage of Two Dune-Building Grasses: Calamagrostis arenaria (L.) Roth and Thinopyrum junceum (L.) Á.Löve - M. D. Cerrato; A. Ribas-Serra; P. M. Mir-Rosselló; I. Cortés-Fernández; C. Douthe; C. Cardona; A. Sureda; J. Flexas; L. Gil (Journal of Plant Growth Regulation, 2024)
Human disturbance and seawater intrusion have unpredictable effects on coastal species. Dune systems are crucial coastal habitats because they provide natural front protection against seawater influence. Adult plant stands in dunes are important since they maintain dune structure. This study evaluated salinity stress responses in adult plants of two key dune-building grasses differing in salt tolerance: Thinopyrum junceum (tolerant) and Calamagrostis arenaria (less tolerant). Cultivated plants were exposed to various seawater (SW) dilutions (Tap-Water, 6.25%, 12.5%, 25%, 50%, and 100%) and gas exchange measurements and oxidative stress biomarkers were determined after two months of treatment. Stress conditions were maintained until flowering to assess effects on the reproductive effort. The reproductive response showed high plasticity at various inflorescence stages in T. junceum , minimizing abortion processes. C. arenaria showed lower plasticity and higher abortion rates. Physiological traits responded similarly to salinity in both species, with greater effect on F v / F m decrease and non-photochemical quenching increase for T. junceum . Biochemical patterns of response were also similar, with increasing enzymatic activities at 25% SW treatment, mainly for glutathione reductase and peroxidase (GSH and GPx), and stress damage occurring at 50% and 100% SW treatments for increased malonaldehyde (MDA) levels. These findings provide insight into the salinity tolerance mechanisms of dune-building grasses. Higher salinity tolerance is suggested for T. junceum based on better reproductive effort. Higher juvenile tolerance, faster growth, and plant cycle adjustments are indicated as key traits for higher salinity tolerance of T. junceum in contrast to C. arenaria .

Salinity tolerance of two critically endangered endemic species and its implications for distribution and conservation of model microinsular Mediterranean species - C. Cardona; I. Cortés-Fernández; M. D. Cerrato; L. Gil (Plant Ecology, 2024)

Kinetics of Na- and K- uranyl arsenate dissolution - Isabel Meza; Noah Jemison; Jorge Gonzalez-Estrella; Peter C. Burns; Virginia Rodriguez; Ginger E. Sigmon; Jennifer E.S. Szymanowski; Abdul-Mehdi S. Ali; Kaelin Gagnon; José M. Cerrato; Peter Lichtner (Chemical Geology, 2023)

Time pattern variation of alien plant introductions in an insular biodiversity hotspot: the Balearic Islands as a case study for the Mediterranean region - M. D. Cerrato; I. Cortés-Fernández; A. Ribas-Serra; P. M. Mir-Rosselló; C. Cardona; L. Gil (Biodiversity and Conservation, 2023)
Allochthonous plant species are considered among the main environmental issues worldwide, being especially accused in the Mediterranean basin. The present study aims to update Balearic Alien Flora and discuss its time and spatial variation and invasiveness. Information regarding allochthonous plant records of the Balearic Islands were gathered and analysed based on published checklists and online databases. For each species several general traits were assigned based on previous references to characterise the alien Balearic Flora. Records of allochthonous species between 1827 and 2023 indicate that Alien Balearic Flora is composed of 624 taxa recorded unevenly among islands, with lower records in smaller islands. Alien flora is mainly composed of therophytes and phanerophytes being held mainly in human related habitats. Introduction pathway is mainly ornamental, with over 50% of taxa entering through gardening and horticultural practices. Main biogeographical origins are American, Mediterranean, Euroasiatic and Cape origins. Invasive status of Balearic alien flora shows that 44% of all taxa can be regarded as casual, while 35% are naturalised, and 17% can be considered invasive, being the latter increased in smaller islands. Time variations trends starting mainly in the 70 s and predictive models show that alien species increase exponentially, being the most represented taxa from synanthropic habitats, introduced as ornamentals, lianas, phanerophytes and therophytes from Cactaceae , Asteraceae and Leguminosae families. The results of the present study can serve as a model to facilitate the scientifically informed decision making and management of plant invasions both in the Balearic Islands and other continental insular systems and Mediterranean regions.

Carotid artery stenting during endovascular thrombectomy for acute ischemic stroke with tandem occlusion: the Italian Registry of Endovascular Treatment in Acute Stroke - Fabrizio Sallustio; Giovanni Pracucci; Manuel Cappellari; Valentina Saia; Alfredo Paolo Mascolo; Federico Marrama; Roberto Gandini; Giacomo Koch; Marina Diomedi; Federica D’Agostino; Alessandro Rocco; Valerio Da Ros; et al. (Acta Neurologica Belgica, 2023)

Evidence of interpopulation variation in the germination of Eryngium maritimum L. (Apiaceae) - I. Cortés-Fernández; M. D. Cerrato; A. Ribas-Serra; C. Cardona; C. González; L. Gil (Plant Ecology, 2021)
Germination is considered as one of the most crucial steps in a plant’s lifetime. The germination of Eryngium maritimum , a dune species located across all European coasts, has been extensively analysed in Northern populations, where it is considered a locally endangered species. However, less attention has been given to southern populations, where the knowledge about the germination of the species is very limited. The main objective of the present study was to analyse the effect of cold stratification in one Mediterranean and one Atlantic population of the species, as well as to compare the potential variation of seed dormancy among a latitudinal gradient in European populations based on current literature. Seeds collected from Mallorca (Mediterranean, Spain) and Asturias (Atlantic, Spain) were germinated at different temperatures and cold stratification periods ranging from 4 to 20 weeks. These results were merged with the results of previous studies to test the potential effect of latitude and climatic variables in germination. Although the optimal incubation temperature was 10 ºC, the highest final germination percentages (up to 96%) was obtained in both populations combining specific cold stratification periods (5 ºC) and constant incubation temperatures (15–20 ºC). Atlantic seeds needed longer cold stratification times to reach high germination percentages compared with Mediterranean seeds. Apart from the stratification response, significant differences in viability and in germination were observed between the Atlantic and the Mediterranean populations. Considering data from previous studies in the analysis, the results suggest that there is a potential effect of latitude in the ecological germination requirements, by which the higher the latitude, the longer the cold stratification period required to germinate, with a correlation with the mean annual temperature. These results suggests that two factors, modulation of dormancy relating to adaptative or maternal effects and viability, govern the germination of the species.

Economic assessment of fidaxomicin for the treatment of Clostridium difficile infection (CDI) in special populations (patients with cancer, concomitant antibiotic treatment or renal impairment) in Spain - C. Rubio-Terrés; J. Cobo Reinoso; S. Grau Cerrato; J. Mensa Pueyo; M. Salavert Lletí; A. Toledo; P. Anguita; D. Rubio-Rodríguez; M. Watt; R. Gani (European Journal of Clinical Microbiology & Infectious Diseases, 2015)

Dispersal and connectivity effects at different altitudes in the Euphydryas aurinia complex - L. P. Casacci; C. Cerrato; F. Barbero; L. Bosso; S. Ghidotti; M. Paveto; M. Pesce; E. Plazio; G. Panizza; E. Balletto; R. Viterbi; S. Bonelli (Journal of Insect Conservation, 2015)

Patterns of biodiversity in the northwestern Italian Alps: a multi-taxa approach - R. Viterbi; C. Cerrato; B. Bassano; R. Bionda; A. Hardenberg; A. Provenzale; G. Bogliani (Community Ecology, 2013)

Rapid multi-analyte quantification of benzophenone, 4-methylbenzophenone and related derivatives from paperboard food packaging - R. Koivikko; S. Pastorelli; A. Rodríguez-Bernaldo de Quirós; R. Paseiro-Cerrato; P. Paseiro-Losada; C. Simoneau (Food Additives & Contaminants: Part A, 2010)

Habitat and age of the giant squid ( Architeuthis sanctipauli ) inferred from isotopic analyses - N. H. Landman; J. K. Cochran; R. Cerrato; J. Mak; C. F. E. Roper; C. C. Lu (Marine Biology, 2004)